Covalent organic framework thin-films for molecular separation - Dey, Kaushik; Banerjee, Rahul (Acta Crystallographica A‐Foundation and Advances, 2014)
Keywords: Covalent organic framework; Separation; Thin-films

Interplaying intrinsic and extrinsic proton conductivities in covalent organic frameworks - Chandra, Suman; Kundu, Tanay; Dey, Kaushik; Addicoat, Matthew A.; Heine, Thomas; Banerjee, Rahul (Chemistry of Materials, 2016)
A sulfonic-acid-based covalent organic framework (TpPa-SO3H) has been synthesized that exhibits intrinsic proton conductivity under anhydrous conditions. The sulfonic acid groups are aligned on the two-dimensional (2D) layers at periodic intervals and promote the proton hopping inside the hexagonal one-dimensional channel. The intrinsic proton conductivity of TpPa-SO3H was measured as 1.7 X 10(-5) S cm(-1) at 120 degrees C under anhydrous conditions. To enhance the proton conductivity, we have synthesized a hybrid COF TpPa(SO3H-Py) by a ligand-based solid-solution approach that contains sulfonic acid as the acidic site, as well as pyridine as the basic site, in order to immobilize acidic proton carrier molecules. Impregnation of phytic acid molecules inside the framework increases the anhydrous proton conductivity up to 5 x 10(-4) S cm(-1) at 120 degrees C. Such an approach highlights the advantage and first-time use of hybrid COF for interplaying intrinsic to extrinsic proton conductivity.

Covalent organic frameworks: chemistry beyond the structure - Kandambeth, Sharath; Dey, Kaushik; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Covalent organic frameworks (COFs) represent a new field of rapidly growing chemical research that takes direct inspiration from diverse covalent bonds existing between atoms. The success of linking atoms in two and three dimensions to construct extended framework structures moved the chemistry of COFs beyond the structures to methodologies, highlighting the possibility of prospective applications. Although structure to property relation in COFs has led to fascinating properties, chemical stability, processability and scalability were some of the important challenges that needed to be overcome for their successful implementation. In this Perspective, we take a closer look at the growth of COFs from mere supramolecular structures to potential industrializable materials.

Covalent self-assembly in two dimensions: connecting covalent organic framework nanospheres into crystalline and porous thin films - Sasmal, Himadri Sekhar; Halder, Arjun; Kunjattu, Shebeeb; Dey, Kaushik; Nadol, Athulya; Ajithkumar, Thalasseril G.; Bedadur, Prachiti Ravindra; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
Insolubility of covalent organic frameworks (COFs) in organic solvents is one of the major obstacles for the potential application of these extended networks such as drug delivery, sensing, optoelectronics, and semiconductor device fabrication. The present work proposes a unique way to make uniform, solution-processable, crystalline, and porous COF nanospheres directly from the homogeneous solution of amine and aldehyde via spatial and temporal control of the nucleation and growth. This strategy of direct nucleation simultaneously showcases the caliber to tune the size of the COF nanospheres from 25 to 570 nm. We have also demonstrated the concept of mesoscale covalent self-assembly of those solution-processable COF nanospheres in the liquid-liquid interface (DCM-water bilayer) for the very first time, transmuting them into self-standing COF thin films with long-range ordered arrangements in two dimensions. The crystalline and porous (with TpAzo showing highest S-BET of 1932 m(2) g(-1)) free-standing COF thin films could be fabricated in a wide range of thicknesses from as low as 21 nm to as high as 630 nm. Both beta-ketoenamine (TpAzo, TpDPP) and imine (TpOMeAzo, TpOMeDPP) linked COF thin films have been synthesized via mesoscale covalent self-assembly of the solution-processable COF nanospheres illustrating the generality of this eloquent methodology. Further, the solution processability has been tested and utilized to cast COF thin films uniformly in the inner and outer surface of an alumina hollow fiber membrane. The COF thin film-alumina hollow fiber membrane composites have showcased promising selective molecular separation of He and O-2, He and CO2, and He and N-2.

Inducing disorder in order: hierarchically porous covalent organic framework nanostructures for rapid removal of persistent organic pollutants - Karak, Suvendu; Dey, Kaushik; Torris, Arun; Halder, Arjun; Bera, Saibal; Kanheerampockil, Fayis; Banerjee, Rahul (Journal of the American Chemical Society, 2019)
The key factor responsible for fast diffusion and mass transfer through a porous material is the availability of a widely open pore interior having complete accessibility from their surface. However, because of their highly stacked nature, ordered two-dimensional (2D) materials fail to find real-world applicability, as it is difficult to take advantage of their complete structure, especially the inner cores. In this regard, three-dimensional (3D) nanostructures constructed from layered two-dimensional crystallites could prove to be advantageous. However, the real challenge is to cultivate a porous nanostructure with ordered pores where the pores are surrounded by crystalline walls. Herein, a simple yet versatile in situ gas-phase foaming technique has been employed to address these cardinal issues. The use of baking soda leads to the continuous effervescence of CO2 during the crystallization of foam, which creates ripples and fluctuations on the surface of the 2D crystallites. The induction of ordered micropores within the disordered 3D architecture synergistically renders fast diffusion of various guests through the interconnected pore network. The high-density defects in the hierarchically porous structure help in ultrafast adsorption (<10 s) of various pollutants (removal efficiency of 99%) from water, all of which would lead to significant environmental benefit. The pseudo-second-order rate constant for the BPA pollutant is 182.3 g mg(-1) min(-1), which is the highest among all the literature reports to date. The high removal efficiency (highest efficiency of 94% and average efficiency of 70%) of a persistent organic pollutant has been attended for the first time.

Porosity switching in polymorphic porous organic cages with exceptional chemical stability - Bera, Saibal; Dey, Kaushik; Pal, Tapan K.; Halder, Arjun; Tothadi, Srinu; Karak, Suvendu; Addicoat, Matthew; Banerjee, Rahul (Angewandte Chemie-International Edition, 2019)
Porous solids that can be switched between different forms with distinct physical properties are appealing candidates for separation, catalysis, and host-guest chemistry. In this regard, porous organic cages (POCs) are of profound interest because of their solution-state accessibility. However, the application of POCs is limited by poor chemical stability. Synthesis of an exceptionally stable imine-linked (4+6) porous organic cage (TpOMe-CDA) is reported using 2,4,6-trimethoxy-1,3,5-triformyl benzene (TpOMe) as a precursor aldehyde. Introduction of the -OMe functional group to the aldehyde creates significant steric and hydrophobic characteristics in the environment around the imine bonds that protects the cage molecules from hydrolysis in the presence of acids or bases. The electronic effect of the -OMe group also plays an important role in enhancing the stability of the reported POCs. As a consequence, TpOMe-CDA reveals exceptional chemical stability in neutral, acidic and basic conditions, even in 12m NaOH. Interestingly, TpOMe-CDA exists in three different porous and non-porous polymorphic forms (, , and ) with respect to differences in crystallographic packing and the orientation of the flexible methoxy groups. All of the polymorphs retain their crystallinity even after treatment with acids and bases. All the polymorphs of TpOMe-CDA differ significantly in their properties as well as morphology and could be reversibly switched in the presence of an external stimulus.
Keywords: chemical stability; Morphology; organic cages; polymorphism; porosity switching

Morphological evolution of two-dimensional porous hexagonal trimesic acid framework - Tothadi, Srinu; Koner, Kalipada; Dey, Kaushik; Addicoat, Matthew; Banerjee, Rahul (ACS Applied Materials & Interfaces, 2020)
Hexagonal single crystal structure (Form II) of trimesic acid (TMA) has been isolated by dissolving the interpenetrated Form I of TMA in tetrahydrofuran. Form II (hexagonal) was converted to Form I (interpenetrated) at room temperature through some intermediate structures. A detailed time-dependent FESEM study shows that the external morphology of Form II (hexagonal) is a hollow hexagonal tube that mimics its crystal structure. The block-shaped (morphology) of Form I (interpenetrated) was converted to the hollow hexagonal tube through some intermediate morphologies which are corresponding to particular crystal structures. Here, we have established a strong correlation between crystal structures with the morphology. These hollow tubes have been employed for Rhodamine B dye adsorption studies and showed an uptake of 82%, much more significant than Form I (interpenetrated) (39%) due to the presence of a pore channel in the crystal structure.
Keywords: dye adsorption; hollow hexagonal rod; hydrogen-bonded organic framework; morphology evaluation; trimesic acid

Nanoparticle size-fractionation through self-standing porous covalent organic framework films - Dey, Kaushik; Kunjattu, Shebeeb H.; Chahande, Anurag M.; Banerjee, Rahul (Angewandte Chemie-International Edition, 2020)
Covalent organic frameworks (COFs) have attracted attention due to their ordered pores leading to important industrial applications like storage and separation. Combined with their modular synthesis and pore engineering, COFs could become ideal candidates for nanoseparations. However, the fabrication of these microcrystalline powders as continuous, crack-free, robust films remains a challenge. Herein, we report a simple, slow annealing strategy to construct centimeter-scale COF films (Tp-Azo and Tp-TTA) with micrometer thickness. The as-synthesized films are porous (SA(BET)=2033 m(2) g(-1) for Tp-Azo) and chemically stable. These COFs have distinct size cut-offs (ca. 2.7 and ca. 1.6 nm for Tp-Azo and Tp-TTA, respectively), which allow the size-selective separation of gold nanoparticles. Unlike, other conventional membranes, the durable structure of the COF films allow for excellent recyclability (up to 4 consecutive cycles) and easy recovery of the gold nanoparticles from the solution.
Keywords: covalent organic frameworks; films; nanofilter; Nanoparticles; size-selective separation

Dual nanomechanics in anisotropic porous covalent organic framework janus-type thin films - Mohata, Shibani; Dey, Kaushik; Bhunia, Surojit; Thomas, Neethu; Gowd, E. Bhoje; Ajithkumar, Thalasseril G.; Reddy, C. Malla; Banerjee, Rahul (Journal of the American Chemical Society, 2022)
Empowered by crystalline ordered structures and homogeneous fabrication techniques, covalent organic frameworks (COFs) have been realized with uniform morphologies and isotropic properties. However, such homogeneity often hinders various surface-dependent properties observed in asymmetric nanostructures. The challenge remains to induce heterogeneity in COFs by creating an asymmetric superstructure such as a Janus thin film. In this regard, we propose a versatile yet straightforward interfacial layer-grafting strategy to fabricate free-standing Janus-type COF-graphene thin films. Herein, two-dimensional graphene sheets were utilized as the suitable grafter due to the possibility of noncovalent interactions between the layers. The versatility of the approach was demonstrated by fabricating two distinct Janus-type films, with the COF surface interwoven with nanofibers and nanospheres. The Janus-type films showcase opposing surface morphologies originating from graphene sheets and COF nanofibers or nanospheres, preserving the porosity (552-600 m(2) g(-1)). The unique surface chemistries of the constituent layers further endow the films with orthogonal mechanical properties, as confirmed by the nanoindentation technique. Interestingly, the graphene sheets favor the Janus-type assembly of COF nanofibers over the nanospheres. This is reflected in the better nanomechanical properties of COFfiber-graphene films (E-gra(phene) = 300-1200 MPa; E-COF( )= 15-60 MPa) compared to the COFsphere-graphene films (E-gra(phe)ne = 11-14 MPa; E-CO(F )= 2-5 MPa). These results indicate a direct relationship between the mechanical properties and homo/heterogeneity of Janus-type COF films.

Covalent organic framework cladding on peptide-amphiphile-based biomimetic catalysts - Kumar Mahato, Ashok; Pal, Sumit; Dey, Kaushik; Reja, Antara; Paul, Satyadip; Shelke, Ankita; Ajithkumar, Thalasseril G.; Das, Dibyendu; Banerjee, Rahul (Journal of the American Chemical Society, 2023)
Peptide-based biomimetic catalysts are promising materialsforefficient catalytic activity in various biochemical transformations.However, their lack of operational stability and fragile nature innon-aqueous media limit their practical applications. In this study,we have developed a cladding technique to stabilize biomimetic catalystswithin porous covalent organic framework (COF) scaffolds. This methodologyallows for the homogeneous distribution of peptide nanotubes insidethe COF (TpAzo and TpDPP) backbone, creating strong noncovalent interactionsthat prevent leaching. We synthesized two different peptide-amphiphiles,C10FFVK and C10FFVR, with lysine (K) and arginine(R) at the C-termini, respectively, which formed nanotubular morphologies.The C10FFVK peptide-amphiphile nanotubes exhibit enzyme-likebehavior and efficiently catalyze C-C bond cleavage in a buffermedium (pH 7.5). We produced nanotubular structures of TpAzo-C10FFVK and TpDPP-C10FFVK through COF claddingby using interfacial crystallization (IC). The peptide nanotubes encasedin the COF catalyze C-C bond cleavage in a buffer medium aswell as in different organic solvents (such as acetonitrile, acetone,and dichloromethane). The TpAzo-C10FFVK catalyst,being heterogeneous, is easily recoverable, enabling the reactionto be performed for multiple cycles. Additionally, the synthesis ofTpAzo-C10FFVK thin films facilitates catalysis inflow. As control, we synthesized another peptide-amphiphile, C10FFVR, which also forms tubular assemblies. By depositingTpAzo COF crystallites on C10FFVR nanotubes through IC,we produced TpAzo-C10FFVR nanotubular structuresthat expectedly did not show catalysis, suggesting the critical roleof the lysines in the TpAzo-C10FFVK.

Covalent organic framework thin-film photodetectors from solution-processable porous nanospheres - Bag, Saikat; Sasmal, Himadri Sekhar; Chaudhary, Sonu Pratap; Dey, Kaushik; Blaette, Dominic; Guntermann, Roman; Zhang, Yingying; Poloz, Miroslav; Kuc, Agnieszka; Shelke, Ankita; Vijayaraghavan, Ratheesh K.; Ajithkumar, Thalasseril G.; et al. (Journal of the American Chemical Society, 2023)
The synthesis of homogeneous covalent organic framework (COF) thin films on a desired substrate with decent crystallinity, porosity, and uniform thickness has great potential for optoelectronic applications. We have used a solution-processable sphere transmutation process to synthesize 300 +/- 20 nm uniform COF thin films on a 2 x 2 cm2 TiO2-coated fluorine-doped tin oxide (FTO) surface. This process controls the nucleation of COF crystallites and molecular morphology that helps the nanospheres to arrange periodically to form homogeneous COF thin films. We have synthesized four COF thin films (TpDPP, TpEtBt, TpTab, and TpTta) with different functional backbones. In a close agreement between the experiment and density functional theory, the TpEtBr COF film showed the lowest optical band gap (2.26 eV) and highest excited-state lifetime (8.52 ns) among all four COF films. Hence, the TpEtBr COF film can participate in efficient charge generation and separation. We constructed optoelectronic devices having a glass/FTO/TiO2/COF-film/Au architecture, which serves as a model system to study the optoelectronic charge transport properties of COF thin films under dark and illuminated conditions. Visible light with a calibrated intensity of 100 mW cm-2 was used for the excitation of COF thin films. All of the COF thin films exhibit significant photocurrent after illumination with visible light in comparison to the dark. Hence, all of the COF films behave as good photoactive substrates with minimal pinhole defects. The fabricated out-of-plane photodetector device based on the TpEtBr COF thin film exhibits high photocurrent density (2.65 +/- 0.24 mA cm-2 at 0.5 V) and hole mobility (8.15 +/- 0.64 x10-3 cm2 V-1 S-1) compared to other as synthesized films, indicating the best photoactive characteristics.

Hierarchical covalent organic framework-foam for multi-enzyme tandem catalysis - Paul, Satyadip; Gupta, Mani; Dey, Kaushik; Mahato, Ashok Kumar; Bag, Saikat; Torris, Arun; Gowd, E. Bhoje; Sajid, Hasnain; Addicoat, Matthew A.; Datta, Supratim; Banerjee, Rahul (Chemical Science, 2023)
Covalent organic frameworks (COFs) are ideal host matrices for biomolecule immobilization and biocatalysis due to their high porosity, various functionalities, and structural robustness. However, the porosity of COFs is limited to the micropore dimension, which restricts the immobilization of enzymes with large volumes and obstructs substrate flow during enzyme catalysis. A hierarchical 3D nanostructure possessing micro-, meso-, and macroporosity could be a beneficial host matrix for such enzyme catalysis. In this study, we employed an in situ CO2 gas effervescence technique to induce disordered macropores in the ordered 2D COF nanostructure, synthesizing hierarchical TpAzo COF-foam. The resulting TpAzo foam matrix facilitates the immobilization of multiple enzymes with higher immobilization efficiency (approximately 1.5 to 4-fold) than the COF. The immobilized cellulolytic enzymes, namely beta-glucosidase (BGL), cellobiohydrolase (CBH), and endoglucanase (EG), remain active inside the TpAzo foam. The immobilized BGL exhibited activity in organic solvents and stability at room temperature (25 degrees C). The enzyme-immobilized TpAzo foam exhibited significant activity towards the hydrolysis of p-nitrophenyl-beta-d-glucopyranoside (BGL@TpAzo-foam: K-m and V-max = 23.5 +/- 3.5 mM and 497.7 +/- 28.0 mu M min(-1)) and carboxymethylcellulose (CBH@TpAzo-foam: K-m and V-max = 18.3 +/- 4.0 mg mL(-1) and 85.2 +/- 9.6 mu M min(-1) and EG@TpAzo-foam: K-m and V-max = 13.2 +/- 2.0 mg mL(-1) and 102.2 +/- 7.1 mu M min(-1)). Subsequently, the multi-enzyme immobilized TpAzo foams were utilized to perform a one-pot tandem conversion from carboxymethylcellulose (CMC) to glucose with high recyclability (10 cycles). This work opens up the possibility of synthesizing enzymes immobilized in TpAzo foam for tandem catalysis.